Introduction to the Special Issue: "Conceptualizing Effective Social Policy Design: Design Spaces and Capacity Challenges". (February 2017) - Chindarkar, Namrata; Howlett, Michael; Ramesh, M
Summary: This article addresses the rise of design thinking and its problematics in the social policy sphere. In particular, it argues that studies of social policy design, like all design work in policymaking, must differentiate more carefully between technical and political considerations in public policymaking and examine the implications each process has for the content of social policy design, its implementation, and its prospects of success or failure. The article develops a model of social policy formulation spaces based on the extent to which policies are intended to address technical or political problems and a government's capacity to engage in policy analysis and alternative assessment. This model is applied in the articles in this special issue to help understand the patterns of policy content and outcome success and failure found in this sector across multiple jurisdictions and issue areas. Copyright © 2017 John Wiley & Sons, Ltd.